Where are female legislators? on political participation and legislative authorities at the subnational level. cases in Entre Ríos and Santa Fe (1983,2022) (Papeles, 2022)
After reviewing the integration of the Chambers of Deputies and Senators in Entre Ríos and Santa Fe from 1983 to 2022 from a perspective of descriptive representation, this article questions the mechanisms that favored the access of women to seats in both provinces, while also observing which positions they held in the organization of parliamentary hierarchies. The article shows that in both provinces the parties or electoral fronts adapted their strategies so that the quota provided for in the regulations becomes the ceiling for female participation instead of a starting point that can be expanded by adding to their ballots more women candidates than the minimum required by law. Therefore, these marginal positions in voting lists are also manifested when power is distributed within parliaments. The article concludes that the existence of gender bias when appointing legislative authorities lies in the fact that this decision is a power that the political forces retain and, consequently, the assignment of hierarchical positions within the Chambers reflects the same gender bias that these hold at the time of forming the lists.
Keywords: Legislative chambers; descriptive representation; legislative authorities; Entre Ríos; Santa Fe